The synthesis and characterization of the 'research chemical' N‐(1‐amino‐3‐methyl‐1‐oxobutan‐2‐yl)‐1‐(cyclohexylmethyl)‐3‐(4‐fluorophenyl)‐1H‐pyrazole‐5‐carboxamide (3, 5‐AB‐CHMFUPPYCA) and differentiation from its 5, 3‐regioisomer. Issue 9 (11th September 2015) - McLaughlin, Gavin; Morris, Noreen; Kavanagh, Pierce V.; Power, John D.; Twamley, Brendan; O'Brien, John; Talbot, Brian; Dowling, Geraldine; Brandt, Simon D.
Abstract : This study presents the identification of N ‐(1‐amino‐3‐methyl‐1‐oxobutan‐2‐yl)‐1‐(cyclohexylmethyl)‐3‐(4‐fluorophenyl)‐1 H ‐pyrazole‐5‐carboxamide that was termed 3, 5‐AB‐CHMFUPPYCA. This compound was obtained from a UK‐based Internet vendor, who erroneously advertised this 'research chemical' as AZ‐037 and which would have been associated with ( S )‐ N ‐(1‐amino‐3‐methyl‐1‐oxobutan‐2‐yl)‐1‐(5‐fluoropentyl)‐5‐(4‐fluorophenyl)‐1 H ‐pyrazole‐3‐carboxamide. The presence of the pyrazole core indicates a bioisosteric replacement of an indazole ring that is frequently associated with synthetic cannabinoids of the PINACA, FUBINACA, and CHMINACA series. The pyrazole ring system present in 3, 5‐AB‐CHMFUPPYCA gives rise to the regioisomer N ‐(1‐amino‐3‐methyl‐1‐oxobutan‐2‐yl)‐1‐(cyclohexylmethyl)‐5‐(4‐fluorophenyl)‐1 H ‐pyrazole‐3‐carboxamide (named 5, 3‐AB‐CHMFUPPYCA) and both isomers were synthesized using two specific routes which supported the correct identification of the 'research chemical' as 3, 5‐AB‐CHMFUPPYCA. Both isomers could be conveniently differentiated. Interestingly, a route specific chlorine‐containing by‐product also was observed during the synthesis of 3, 5‐AB‐CHMFUPPYCA and identified as N ‐(1‐amino‐3‐methyl‐1‐oxobutan‐2‐yl)‐4‐chloro‐1‐(cyclohexylmethyl)‐3‐(4‐fluorophenyl)‐1 H ‐pyrazole‐5‐carboxamide. An extensive analytical characterization included chromatographic, spectroscopic, mass spectrometric platforms as well as crystal structure analysis. The syntheses and analytical characterizations of both AB‐CHMFUPPYCA isomers are reported for the first time and serves as a reminder that the possibility of mislabeling of 'research chemicals' cannot be excluded. The pharmacological activities of both AB‐CHMFUPPYCA isomers remain to be explored. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This study presents the identification of N ‐(1‐amino‐3‐methyl‐1‐oxobutan‐2‐yl)‐1‐(cyclohexylmethyl)‐3‐(4‐fluorophenyl)‐1 H ‐pyrazole‐5‐carboxamide (3, 5‐AB‐CHMFUPPYCA). This compound was obtained from a UK‐based Internet vendor, who erroneously advertised this 'research chemical' as AZ‐037. 3, 5‐AB‐CHMFUPPYCA, along with its regioisomer N ‐(1‐amino‐3‐methyl‐1‐oxobutan‐2‐yl)‐1‐(cyclohexylmethyl)‐5‐(4‐fluorophenyl)‐1 H ‐pyrazole‐3‐carboxamide (5, 3‐AB‐CHMFUPPYCA) were synthesized using two specific routes, which supported the correct identification of the 'research chemical' as 3, 5‐AB‐CHMFUPPYCA. An extensive analytical characterization included chromatographic, spectroscopic, mass spectrometric platforms as well as crystal structure analysis.